2013
DOI: 10.1111/acv.12043
|View full text |Cite
|
Sign up to set email alerts
|

Trophy hunting inAfrica: long‐term trends in antelope horn size

Abstract: Trophy hunting in ungulates may favour individuals with smaller horns. A decrease in horn/antler size may jeopardize the conservation potential of hunting areas, which would be a major concern in Africa where hunting zones represent over half of the total area of protected lands. We investigated horn length trends of harvested male impalas Aepyceros melampus, greater kudus Tragelaphus strepsiceros and sable antelopes Hippotragus niger, from 1974 to 2008 in Matetsi Safari Area, Zimbabwe. Horn length declined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 47 publications
6
52
2
Order By: Relevance
“…To the best of our knowledge, no previous studies have reported the SCI minimum scores for most species to compare with our findings. Impala trophy size trends declined significantly over time and these are comparable to findings observed in Zimbabwe [30] and South Africa [25]. The contribution of illegal hunting [59] on the declining trophy size trends may be minimal given that subsistence hunters kill indiscriminately and do not select for trophy size [76,77].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…To the best of our knowledge, no previous studies have reported the SCI minimum scores for most species to compare with our findings. Impala trophy size trends declined significantly over time and these are comparable to findings observed in Zimbabwe [30] and South Africa [25]. The contribution of illegal hunting [59] on the declining trophy size trends may be minimal given that subsistence hunters kill indiscriminately and do not select for trophy size [76,77].…”
Section: Discussionsupporting
confidence: 55%
“…Although the significance of trophy hunting in Africa is well documented, very little attention has been given to trends in trophy quality in African wildlife species other than lions (Panthera leo) [25,[29][30][31][32]. In Zimbabwe, a decline in the trophy quality of three hunted gregarious herbivores, impala (Aepyceros melampus), greater kudu (Tragelaphus strepsiceros) and sable (Hippotragus niger) in Matetsi hunting area has been noticed [30].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is reasonable to expect gene flow from harvest refuges to protected areas, but only for males that survive the hunting season. Our results underline the need for research on the amount and timing of genetic exchange among protected and hunted areas in terrestrial environments, not only for mountain sheep but also for other species that face similar landscapes with varying degrees of selective harvest (Crosmary et al, ; Loveridge et al, ).…”
Section: Discussionmentioning
confidence: 56%
“…Most of the experts viewed the quota setting process in Zimbabwe as overly relaying on opinions of stakeholders and not based on the monitoring data on population sizes thus compromising the sustainability of the process. Similarly there have been reports on the decline in trophy size of hunted species in some cases in Zimbabwe [97] as has also been the case with other regional countries, that is, South Africa [98,99,135], western Tanzania [136], and Zambia [137]. It is somehow believed that there seems to be a lack of implementation of age based harvesting strategies as required by the Zimbabwean policies on trophy hunting [58].…”
Section: Emerging Issues In Trophy Hunting Industry and Futurementioning
confidence: 84%
“…However, more effort needs to be put towards law enforcement as there has been a challenge of illegal hunting activities in some parts of Zimbabwe which has triggered much despondence and negative media framing [84,95,96]. A concerted effort towards monitoring animal populations, illegal off-takes, and trophy quality is critical for the sustainability of trophy hunting [97][98][99]. This information would provide essential scientific information required for adaptive management in lobbying and rebranding trophy hunting activities in these areas for the good of conservation [3].…”
Section: Trophy Hunting In Campfire Areasmentioning
confidence: 99%